Coastal Women's Community Resilience Model as a Disaster Mitigation Effort; inspired by the Motherschool's Program from Women without Borders - Bunga Aprillia (Universitas Budi Luhur, 2026)
Abstract: Indonesia's coastal areas are highly vulnerable to tsunamis, which disproportionately impact women. Coastal women play multiple roles in the domestic, economic, and social spheres of the community, thus holding a strategic position in strengthening family resilience. This study aims to formulate a model for strengthening the capacity of coastal women based on a women's community approach, derived from the Motherschool’s learning model developed by Women without Borders, an Austrian NGO. This model can support tsunami disaster risk reduction in coastal areas through women's movements. The study employed a qualitative approach, with data collection techniques including literature review and interviews. The results indicate that strengthening the capacity of coastal women through group learning can improve risk understanding, family preparedness, and community social networks. The resulting model is structured at three learning levels: micro, meso, and macro. This research contributes to the development of gender-based disaster studies and provides practical implications for the formulation of community-based disaster risk reduction policies. Abstrak: Kawasan pesisir Indonesia sangat rentan terhadap tsunami, yang memberikan dampak secara tidak proporsional terhadap perempuan. Perempuan pesisir memainkan berbagai peran dalam ranah domestik, ekonomi, dan sosial masyarakat, sehingga memiliki posisi strategis dalam memperkuat ketahanan keluarga. ​Penelitian ini bertujuan untuk merumuskan model penguatan kapasitas perempuan pesisir berdasarkan pendekatan komunitas perempuan, yang diadaptasi dari model pembelajaran Motherschool hasil pengembangan Women without Borders, sebuah LSM asal Austria. Model ini dapat mendukung pengurangan risiko bencana tsunami di wilayah pesisir melalui gerakan perempuan. ​Penelitian ini menggunakan pendekatan kualitatif, dengan teknik pengumpulan data meliputi tinjauan pustaka dan wawancara. Hasil penelitian menunjukkan bahwa penguatan kapasitas perempuan pesisir melalui pembelajaran kelompok dapat meningkatkan pemahaman risiko, kesiapsiagaan keluarga, dan jejaring sosial masyarakat. Model yang dihasilkan disusun dalam tiga tingkatan pembelajaran: mikro, meso, dan makro. Penelitian ini berkontribusi pada pengembangan studi bencana berbasis gender dan memberikan implikasi praktis bagi penyusunan kebijakan pengurangan risiko bencana berbasis komunitas.